Analisis Strategi Pemungutan Retribusi Kebersihan Sampah Rumah Tangga Dalam Meningkatkan Pendapatan Asli Daerah Di Kota Bekasi Tahun 2021-2022 - Priadi, Ida Falahira; Subagiyo, Agus (Jurnal Ilmu Administrasi Publik, 2024)
The purpose of this study is to determine and analyze how the Household Waste Retribution Collection Strategy in Increasing Regional Original Revenue in Bekasi City in 2021-2022. The method used is qualitative with a descriptive type of research that produces precise and systematic descriptions. Data collection techniques are interviews and documentation. The implementation of waste retribution collection in Bekasi Regency has great potential because of the high revenue over time the revenue still exceeds the target in 2020-2021. But in 2022 the revenue decreased even though it was still very good because it still reached 99.02%. Efforts from the obstacles experienced by the government, namely conducting intense and comprehensive socialization, a humanist approach to the village community, providing understanding to the community regarding the importance of waste collection levies to develop the region, adding human resources or workers who collect waste and take it to the landfill. when the community is comfortable, the community will automatically continue to use the facility and that way it will have the potential to increase local revenue.